The role of meaning and purpose in the career development of adolescents: a qualitative study - McLaren, Molly, author; Dik, Bryan, advisor; Steger, Michael, committee member; Banning, James, committee member; Aloise-Young, Patricia, committee member (Colorado State University. Libraries, 2011)
The purpose of this qualitative investigation was to explore the role of meaning and purpose in adolescent career development by examining 7th-grade students' responses to a semi-structured interview. Interviews were analyzed using interpretative phenomenological analysis (IPA) methods as described by Willig (2001). The findings supported the vast majority of the literature on the topic, contrasted with a few areas, and expanded others. In general, most participants had heard of the concepts of meaning and purpose in work, as well as the concept of a calling; however, many of them had not thought extensively about these topics. The students offered a variety of descriptions and definitions for each of these concepts. Continued research on the roles of meaning and purpose, and the infusion of meaning and purpose, in childhood career development can contribute to the theoretical knowledge base and practical applications of career curricula and counseling practice.
Keywords: adolescents; career; children; meaning; purpose; vocational